2013
DOI: 10.1007/s00404-013-2959-9
|View full text |Cite
|
Sign up to set email alerts
|

Value of follicular fluid vitamin D in predicting the pregnancy rate in an IVF program

Abstract: Purpose This study investigated whether there is a correlation between levels of 25OH-D in the follicular fluid and the serum of infertile women and the results of IVF and rates of pregnancy. The association between the levels of 25OH-D in the follicular fluid and the vitamin D repletion status was also assessed. Methods Two hundred and twenty-one infertile women participated in an IVF cycle from 2010 to 2011 in a prospective observational study. Serum and follicular fluid were collected for vitamin D analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
68
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 25 publications
13
68
1
6
Order By: Relevance
“…117 However, the above observation is in contrast to the detrimental effects of vitamin D deficiency on the endometrium reported in previous studies. [110][111][112]116 Additionally, two Iranian studies 118,119 failed to demonstrate any significant association between serum or FF vitamin D levels and implantation or pregnancy rates. However, the high prevalence of vitamin D deficiency in the examined population limits the strength of their research.…”
Section: Vitamin D and In Vitro Fertilization (Ivf)mentioning
confidence: 99%
“…117 However, the above observation is in contrast to the detrimental effects of vitamin D deficiency on the endometrium reported in previous studies. [110][111][112]116 Additionally, two Iranian studies 118,119 failed to demonstrate any significant association between serum or FF vitamin D levels and implantation or pregnancy rates. However, the high prevalence of vitamin D deficiency in the examined population limits the strength of their research.…”
Section: Vitamin D and In Vitro Fertilization (Ivf)mentioning
confidence: 99%
“…In a prospective cohort study, vitamin D (25OH-D) serum and follicular fluid levels were analyzed in 82 infertile women undergoing ART. They found that fertilization rate decreased significantly and the implantation rate increased (not significantly) with increasing levels of 25OH-D [89]. Using the same approach, Farzadi et al reported a correlation between follicular fluid 25(OH) D concentration and assisted reproductive outcomes in an Iranian population [90].…”
Section: Vitamin D and Reproductionmentioning
confidence: 94%
“…Ek olarak, hamilelik oranı ile serum ve foliküler sıvı vitamin D düzeyleri (p=0,094, p=0,170, sırasıyla) arasında bir ilişki kurulamamış, bu durum yeterli vitamin D düzeylerine sahip kadınların ancak %7,2 gibi düşük bir oranda olmasıyla açık-lanmıştır. 113 Estes ve ark. (2010) ise İVF'de başarı sağlayanların foliküler sıvılarında DBP ekspresyonunun düşük olduğunu göstermişlerdir.…”
Section: Vi̇tami̇n D Ve In Vi̇tro Ferti̇li̇zasyonunclassified